Departure Passenger Flow Simulation: Case Study on Izmir Adnan Menderes Airport Pre and Post COVID-19 - Savaş S. ATEŞ; Gökhan KOÇ; Talha KOÇ; Mustafa BOLAT (International Journal of Applied Methods in Electronics and Computers, 2021)
The flow of departing passengers from the airport inside the terminal is affected by strategic and tactical decisions of airport operation teams. The decisions made by the managers regarding opening and closing times of check-in, boarding, and gates are critical to optimize the performance of the terminal operation. In this research, Izmir Adnan Menderes Airport was taken as a use case.Departure terminal building of check-in, security control, and boarding gates was taken as the focus entities.The simulation passenger input data were produced for check-in, security, and boarding gates using different distribution probability methodologies to match the actual data. Three days of data (300 flights, 3 thousand passengers) has been derived with the help of a custom generator. A unique simulation tool called Departure Passenger Flow Simulator (DPFs) has been developed for research. Due to manage passenger flow pre and post COVID-19, the opening and closing times of assets (check-in and gates) were simulated in 6 iterations in DPFs in 3 different scenarios. As a result of the research, it was understood that the resources for Izmir Adnan Menderes Airport were sufficient, considering the COVID-19 measures published by the European Aviation Safety Agency (EASA) and the General Directorate of Civil Aviation.